Pion and [eta]-meson mass splitting at the two-flavor chiral crossover - Heller, Markus; Mitter, Mario (Physical review, 2016)
We study the splitting in the screening mass of pions and the η-meson across the chiral crossover. This splitting is determined by the ’t Hooft determinant. We use results for the renormalization group scale dependence of the ’t Hooft determinant obtained within the functional renormalization group in quenched QCD with two flavors. The scale dependence of the ’t Hooft determinant is mapped to its temperature dependence with the help of a Polyakov-quark-meson model. As a result we obtain the temperature dependence of the splitting in the screening mass of pions and the η-meson.
Gesehen am 12.05.2020
Im Titel ist "eta" als griechischer Buchstabe dargestellt